Statistical Evaluation of a Heat Exchanger for Different Fluid Flow Parameters - Chowdhury, B.; Mohan, S. K.; Saikia, B.; Sahu, P. P. (Journal of Scientific Research, 2026)
Heat exchangers are employed extensively in different industries such as ship building, chemical technology, power, food and beverage, and others. Maximum heat transfer in a heat exchanger is desired to achieve the highest possible efficiency and performance of the device. The heat transfer dynamics of a shell and tube heat exchanger with water as the heat transfer fluid are statistically examined in this study using the Full Factorial Design of Experiments approach. Input variables include the fluid flow parameters namely mass flow rates of the hot and cold water (50-250 L/h) as well as the temperature of the hot fluid entering (48.1-66 °C). The responses evaluated are the log mean temperature difference, heat transfer rate, effectiveness and overall heat transfer coefficient. The findings indicate that high flow rates and a high inlet temperature are the optimal input settings for maximum heat transfer. Low flow rates and high inlet temperature are the best settings for maximum effectiveness. The interactions between flow rates have a significant impact on the responses of heat transfer rate, overall heat transfer coefficient, and effectiveness. Effectiveness is also affected by the interaction of cold fluid’s flow rate and its inlet temperature.